Post-tonsillectomy pain management in pediatric patients-a review - Swain, Santosh Kumar (International Journal of Contemporary Pediatrics, 2021)
Tonsillectomy is a common surgical procedure performed in the pediatric age group. Although tonsillectomy is a safe surgery, it is associated with significant post-operative pain. Analgesia after tonsillectomy is often inadequate. Severe post-tonsillectomy throat pain has been described for more than a decade. Parents often worry for handling the pain of their children in home. Post-tonsillectomy pain is often considered as a long lasting and intense in nature. Post-tonsillectomy pain in children is an important problem which overstrains the patient, family and hospital staff. Post-tonsillectomy pain in children is an important problem which overstrains the patient, family and hospital staff. Regulatory alteration in the analgesic armamentarium, particularly in pediatric patients are making the treatment of post-tonsillectomy pain more difficult. Post-tonsillectomy pain in pediatric patients continues to be highly debated clinical issue and also an area of active research. Post-tonsillectomy pain can result in significant morbidity among pediatric patients. There are several analgesics available; each one has its own risk profile and unique side effects when used in pediatric age group in post-tonsillectomy period. This review article provides an update on recent management of post-tonsillectomy pain in pediatric patients. This article reviews the epidemiology, pathophysiology, impact of post-tonsillectomy pain in children and details of medications used for controlling post-tonsillectomy pain.